Biomechanical analysis of three tennis serve types using a markerless system - Abrams, G. D.; Harris, A. H. S.; Andriacchi, T. P.; Safran, M. R. (British Journal of Sports Medicine, 2014)
Purpose: The tennis serve is commonly associated with musculoskeletal injury. Advanced players are able to hit multiple serve types with different types of spin. No investigation has characterised the kinematics of all three serve types for the upper extremity and back. Methods: Seven NCAA Division I male tennis players performed three successful flat, kick and slice serves. Serves were recorded using an eight camera markerless motion capture system. Laser scanning was utilised to accurately collect body dimensions and data were computed using inverse kinematic methods. Results: There was no significant difference in maximum back extension angle for the flat, kick or slice serves. The kick serve had a higher force magnitude at the back than the flat and slice as well as larger posteriorly directed shoulder forces. The flat serve had significantly greater maximum shoulder internal rotation velocity versus the slice serve. Force and torque magnitudes at the elbow and wrist were not significantly different between the serves. Conclusions: The kick serve places higher physical demands on the back and shoulder while the slice serve demonstrated lower overall kinetic forces. This information may have injury prevention and rehabilitation implications.